Socially excessive bankruptcy costs and the benefits of interest rate ceilings on loans - Marco A. Espinosa-Vega; Bruce D. Smith (Federal Reserve Bank of Atlanta, 2001)
The authors study the capital accumulation and welfare implications of ceilings on loan interest rates in a dynamic general equilibrium model. Binding ceilings on loan rates reduce the probability of bankruptcy. Lower bankruptcy rates result in lower bankruptcy and liquidation costs. The authors state conditions under which the resources freed by this cost-saving result increase the steady state capital stock, reduce steady state credit rationing, and raise the steady state welfare of all agents. The authors also argue that the conditions stated are likely to be satisfied in practice. Finally, their results hold even if initially there is capital over-accumulation.
Keywords: 330; Loans; Interest rates; Bankruptcy